2002
DOI: 10.1093/ajcn/76.2.384
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating body fat in girls and female adolescents: advantages and disadvantages of dual-energy X-ray absorptiometry

Abstract: DXA is an appropriate method for estimating body composition in a group of young females because its bias and limits of agreement are independent of age, ethnicity, and body fatness. However, the limits of agreement of 6.7% could cause an individual FM value to be underestimated or overestimated by 28% relative to the 4-compartment value. Therefore, DXA may not be the optimal method of measuring the body fatness of young females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
77
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 30 publications
11
77
0
1
Order By: Relevance
“…Previous studies have shown that DXA measures adiposity with variable bias, tending to overestimate fat mass in those who are fatter. 36,37 Despite such inaccuracy in absolute values, DXA tends to rank fatness consistently with other techniques, and the technique is unlikely to have generated erroneous associations in our analyses. Total fat mass by DXA was very strongly associated with 4-component values in this study (r ¼ 0.98).…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have shown that DXA measures adiposity with variable bias, tending to overestimate fat mass in those who are fatter. 36,37 Despite such inaccuracy in absolute values, DXA tends to rank fatness consistently with other techniques, and the technique is unlikely to have generated erroneous associations in our analyses. Total fat mass by DXA was very strongly associated with 4-component values in this study (r ¼ 0.98).…”
Section: Discussionmentioning
confidence: 87%
“…Although DXA is considered a valid technique for %FM and FM analysis, it is not considered as the 'gold reference' method and it is not without limitations regarding both the accuracy and the reliability to estimate total body fatness. (Wong et al, 2002;Williams et al, 2006). However, of the available methods to measure body composition, DXA has a good performance criteria to measure %FM and FM when compared with multicompartment models (Lohman et al, 2000;Genton et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, under-or overestimations of percent FM that should lead to critical interpretation of data have been reported in young children 12 and in girls. 14 Dramatic changes in body composition occur during adolescence and differ between boys and girls. We therefore conducted this study to examine the effects, in each sex, of diet combined with physical exercise training intervention on the total and segmental body composition in adolescents with severe obesity.…”
Section: Discussionmentioning
confidence: 99%
“…9 The dual-energy X-ray absorptiometry (DEXA) has been validated as an efficient tool to assess the total and regional body composition in vivo, 10 in adults 11 and in children. [12][13][14] Changes in body composition differs markedly between boys and girls during puberty. Hormonal changes that influence patterns in body fat accumulation and lean body mass leading to opposite trends in boys and girls have been well described in nonobese adolescents.…”
Section: Introductionmentioning
confidence: 99%